Analisis Kesesuaian dan Daya Dukung Kawasan Wisata Selam dan Snorkeling di Pantai Jemeluk, Karangasem, Bali - Hadiyanti, Alfi Rizki; Wiyanto, Dwi Budi; Darmendra, I Putu Yogi (Universitas Trunojoyo Madura, 2024)
The abundant biodiversity at Jemeluk Beach does not guarantee that all marine tourism activities and activities do not damage and have a negative impact on the environment. The tourism potential of Jemeluk Beach is the existence of coral reefs and many types of reef fish so that it is suitable to be used as marine tourism, one of which is diving and snorkeling. This research aims to analyze the suitability index and carrying capacity of diving and snorkeling tourism at Jemeluk Beach in order to become a well-managed tourist attraction and develop in the sustainability corridor. The analysis used in this research is the analysis of the suitability and carrying capacity of the area, namely by comparing the characteristics and quality of land against land use requirements for certain tourism activities while still paying attention to the capacity of the area to accommodate tourism activities in order to maintain environmental sustainability and natural preservation. The method of measuring coral reefs using the UPT (Underwater Photo Transect) method which is based on the shape of coral growth. Measurement of the type and number of reef fish was studied using the UVC (Underwater Visual Census) method by taking data along 50 meters at the same depth as the data collection of coral reef cover. The condition of the suitability of diving tourism at points I, II and III has the same value of 1.6 and is classified as unsuitable. In contrast to diving tourism, the condition of the suitability of snorkeling tourism at points I and II has the same value of 2.1 and is classified as suitable category, while point III has a value of 2.48 and is classified as suitable category to be used as an object of marine tourism development. The results of the calculation of the carrying capacity of the area for diving tourism that can be accommodated as many as 404 people/day while snorkeling tourism is 31 people/day.